KEPUTUSAN PETANI BERUSAHATANI PADI SAWAH DI MERAUKE (Studi Kasus Pada Petani Padi Sawah di Kecamatan Kurik Kabupaten Merauke) - Yayat Sukayat; M. Gunardi Judawinata; Rani Andriani Budi Kusumo (Universitas Galuh, 2023)
Rice is a basic need for some Indonesian people. One of the policies to increase paddy rice production carried out by the government during the Old Order and the New Order era was the intensification and extensification program. Development programs through extensification are mainly carried out outside Java through the transmigration program. One of the provinces that have carried out rice field extensification by inviting transmigrants in Papua Province, especially Merauke Regency. Lowland rice production in 2021 will reach 199,214.00 tonnes, making it worthy of being called a rice barn in eastern Indonesia. The main contributors to this increase in production are transmigrant farmers from Java. Javanese farmers are known as farmers whose social exchange values are dominant in farming. But the reality is that in the transmigration area, paddy rice farming activities are full of high technology, and all farmers sell their produce in rice. The question arises, what drives farmers to make these decisions? Are these farmers rational? This research aims to know the farmer's decision to cultivate lowland rice. This research is qualitative with a case study technique in Kurik District, Merauke Regency. The analysis used is descriptive. The results of the research on farmers' decision to cultivate paddy according to their ancestral knowledge, government program to make the location for paddy fields, economic motivation and instrumental rationality.